Analysis of Factors Causing Work Accidents Using the Root Cause Analysis (RCA) Method at the Sumber Asih 1 Bitung Clinic - Azteria, Veza; Hasibuan, Meri; Desyawati Utami; Raya; Gisely Vionalita (Window of Health : Jurnal Kesehatan, 2024)
Work accidents are unexpected events that can result in property loss and loss of life. Occupational safety and health in health installations are defined as activities to guarantee and protect the safety and health of human resources in health installations, patients, and patient companions so that protection standards are created for workers in health installations to prevent and reduce the risk of these dangers. The research was conducted at the Sumber Asih 1 Bitung Clinic in August – December 2023. Based on data on accidents at the Sumber Asih 1 Bitung clinic last year, there were ten work accidents. This research analyzes factors related to work accidents at the Sumber Asih 1 Bitung clinic in 2023. The method used in this research is the root cause analysis (RCA) method with five why analysis. The data source for this research consisted of 4 workers at the Sumber Asih 1 Bitung clinic. The data collection technique uses the observation method and in-depth interviews, followed by the triangulation method to validate the research results. The research found that the causes of work accidents were environmental factors: Lack of lighting in several clinic areas, slippery floors, and limited movement space. Meanwhile, human factors include unsafe actions, Lack of work safety training, Lack of concentration at work, and Lack of awareness of workers using personal protective equipment. It is necessary to carry out K3 (Occupational Safety and Health) training so that workers know the importance of working safely.